Do knowledge infrastructure facilities support Evidence-Based Practice in occupational health? An exploratory study across countries among occupational physicians enrolled on Evidence-Based Medicine courses - van Dijk Frank JH; Sluiter Judith K; Nieuwenhuijsen Karen; Hugenholtz Nathalie IR (BMC, 2009)
Abstract Background Evidence-Based Medicine (EBM) is an important method used by occupational physicians (OPs) to deliver high quality health care. The presence and quality of a knowledge infrastructure is thought to influence the practice of EBM in occupational health care. This study explores the facilities in the knowledge infrastructure being used by OPs in different countries, and their perceived importance for EBM practice. Methods Thirty-six OPs from ten countries, planning to attend an EBM course and to a large extent recruited via the European Association of Schools of Occupational Medicine (EASOM), participated in a cross-sectional study. Results Research and development institutes, and knowledge products and tools are used by respectively more than 72% and more than 80% of the OPs and they are rated as being important for EBM practice (more than 65 points (range 0-100)). Conventional knowledge access facilities, like traditional libraries, are used often (69%) but are rated as less important (46.8 points (range 0-100)) compared to the use of more novel facilities, like question-and-answer facilities (25%) that are rated as more important (48.9 points (range 0-100)). To solve cases, OPs mostly use non evidence-based sources. However, they regard the evidence-based sources that are not often used, e.g. the Cochrane library, as important enablers for practising EBM. The main barriers are lack of time, payment for full-text articles, language barrier (most texts are in English), and lack of skills and support. Conclusion This first exploratory study shows that OPs use many knowledge infrastructure facilities and rate them as being important for their EBM practice. However, they are not used to use evidence-based sources in their practice and face many barriers that are comparable to the barriers physicians face in primary health care.